TRANSCRANIAL MAGNETIC STIMULATION: CLINICAL APPLICATION AND SCIENTIFIC PERSPECTIVES - Tukhtanazarova Shavkiya Ibatovna; Saidmurodov Makhmudali Suratzoda (Scholar Express Journals, 2023)
Transcranial magnetic stimulation (TMS) is a method of neurostimulation and neuromodulation based on electrical induction of an electronic field in a given area of the brain. Since the 1990s attention to TMS has been growing steadily, because this method is considered noninvasive and potentially has broad diagnostic and therapeutic probabilities: the number of publications devoted to TMS
Keywords: transcranial magnetic stimulation; electric field